Brainstorming (Tufts Archival Research Center, 2007)
Handwritten; Illegible/Difficult to Read; List of ideas to fight anti-smoking advocacy. Aims to depoliticize, privatize, and diffuse the public smoking issue, to broaden the issue as one of personal hygeine, and to "obfuscate the issue."